A Distributed Differential Space-Time Coding Scheme With Analog Network Coding in Two-Way Relay Networks - Huo, Qiang; Song, Lingyang; Li, Yonghui; Jiao, Bingli (IEEE transactions on signal processing, 2012)
In this correspondence, we consider general two-way relay networks (TWRNs) with two source and N relay nodes. A distributed differential space time coding with analog network coding (DDSTC-ANC) scheme is proposed. A simple blind estimation and a differential signal detector are developed to recover the desired signal at each source. The pairwise error probability (PEP) and block error rate (BLER) of the DDSTC-ANC scheme are analyzed. Exact and simplified PEP expressions are derived. To improve the system performance, the optimum power allocation (OPA) between the source and relay nodes is determined based on the simplified PEP expression. The analytical results are verified through simulations.